2012
DOI: 10.1115/1.4006308
|View full text |Cite
|
Sign up to set email alerts
|

Active Flow Control Concepts on a Highly Loaded Subsonic Compressor Cascade: Résumé of Experimental and Numerical Results

Abstract: This paper presents experimental and numerical results for a highly loaded, low speed, linear compressor cascade with active flow control. Three active flow control concepts employing steady jets, pulsed jets, and zero mass flow jets (synthetic jets) are investigated at two different forcing locations: at the end walls and the blade suction side. Investigations are performed at the design incidence for jet-to-inlet velocity ratios of approximately 0.7 to 3.0 and two different Reynolds numbers. Detailed flow fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Zaki et al [7] used direct numerical simulation methods to research bypass transition and separation-induced transition in compressor cascades, showing the flow mechanism of bypass transition which appeared on the pressure surfaces of blades and explaining the effect of the pressure gradient on blade surfaces on the start and reattachment in the transition process. Gmelin et al [8] experimentally and numerically studied the effect of three active flow control methods including a stable jet, pulsed jet and zero mass jet on the flow and performance of the compressor and compared the methods' transition locations and geometry on the suction surface. Gbadebo et al [9] researched the effect of boundary layer suction on three-dimensional separation.…”
Section: Introductionmentioning
confidence: 99%
“…Zaki et al [7] used direct numerical simulation methods to research bypass transition and separation-induced transition in compressor cascades, showing the flow mechanism of bypass transition which appeared on the pressure surfaces of blades and explaining the effect of the pressure gradient on blade surfaces on the start and reattachment in the transition process. Gmelin et al [8] experimentally and numerically studied the effect of three active flow control methods including a stable jet, pulsed jet and zero mass jet on the flow and performance of the compressor and compared the methods' transition locations and geometry on the suction surface. Gbadebo et al [9] researched the effect of boundary layer suction on three-dimensional separation.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that passive flow control using vortex generators can reduce total pressure losses by affecting the corner separation at the crossing of the wall and blade [2,3]. It was reported also that active flow control using blowing, suction or synthetic jets can decrease greatly the total pressure losses by removing the corner separation [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this combination of blowing becomes more efficient when changing the blowing mass flow rate. Gmelin et al [6] investigated active flow control on a highly loaded subsonic compressor cascade using both numerical and experimental approaches. The active flow technique consists of three concepts of steady jets, pulsed jets, and zero mass flow jets (synthetic jets), in two different locations: at the endwall and the blade suction side.…”
Section: Introductionmentioning
confidence: 99%
“…Just to name a few among the numerous works, typical flow control applications include boundarylayer blowing or suction to suppress the separation [20], trailing-edge blowing [21], shockwave/boundary-layer interaction control [22], circulation control for lift enhancement [23], etc. Also, optimizations have been applied to FC designs by a number of researchers.…”
mentioning
confidence: 99%